Critical Conversations: Basic Skills Students at the Table - Stanford T. Goto; Marcia Leister (Adult Education Research Conference, 2010)
“I am 44 years old and enrolled in the ABE class at Bellingham Technical College. The ABE class is very important to me right now in my life, while I am drawing unemployment. I dropped out when I was 16 and got married and had my first baby. So there is a lot of stuff I have forgotten. And with the help of the ABE class, I feel like I can do the stuff I thought I couldn't. The ABE class made me have more confidence and self-esteem about myself, with the help of everyone in class.”